Distiribusi Spasial Habitat Bentik dan Substrat di Pantai Ngurbloat Memanfaatkan Data Allen Coral Atlas - Awayal, Dion Dollan; Lekatompessy, Vanela Chatrin; Silaban, Rosita; Elake, Alexander Yosep; Nanlohy, Pieldrie (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
Ngurbloat Beach, located in the Kei Islands, Maluku Province, has a varied coastal ecosystem, including benthic habitats that play an important role in ecological balance and sustainability of marine resources. This study aims to map the spatial distribution of benthic habitats including substrates in the waters of Ngurbloat Beach by utilizing Allen Coral Atlas data. The analysis was conducted through classification of high-resolution satellite images using remote sensing and geographic information system (GIS) methods. The results showed that the total mapped area was 183 ha. Benthic habitats in this area are dominated by coral reefs (18.99%), seagrasses (0.85%), microalgae (2.93%) and sand substrates (16.42%), rocks (39.44%) and dead corals (22.7%). Oceanographic factors and anthropogenic activities in the waters of Ngurbloat Beach affect the distribution of benthic habitats, especially coral reefs that have suffered serious damage and need to be rehabilitated. The utilization of Allen Coral Atlas data proved effective in providing accurate spatial data for benthic ecosystem mapping, which can support conservation efforts and sustainable management of coastal resources.